GENES ASSOCIATED WITH THE DEVELOPMENT OF ISCHEMIC HEART DISEASE (Experimental biology, 2016)
The search of the genes-candidates associated with the development of ischemic heart disease is conducted. A database of genes associated with the development of ischemic heart disease is created and the functions of these genes analyzed in a comparative aspect. It has been shown that many of the genes involved in the development of ischemic heart disease also associated with the development of other cardiovascular diseases: myocardial infarction, hypertension, atherosclerosis, metabolic syndrome. These genes participating in different social meaningful diseases is analyzed. A database of genes associated with the development of ischemic heart disease is the basis for the identification of genes which expression is dependent on the action of microRNAs. The features of the resulting database of genes in the development of ischemic heart disease early diagnostics methods, using molecular genetic markers are discussed.
Keywords: ischemic heart disease; gene; microRNA; mRNA; diagnostics.